Strict Liabilty for Environmental Damage Post the Work Creation Law - Aida Dewi (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2022)
This study aims to analyze the reduction of the meaning of the principle of strict liability in the Omnibuslaw Act which will have a significant impact on environmental law enforcement in Indonesia. Environmental law enforcement will revert back to law enforcement in the past. The research used is normative legal research, with a statute approach. The results of the study indicate that the Omnibus Law abolishes the element "without the need to prove the element of error". The blurring of norms in this regulation actually distances the meaning of the principle of strict liability. Basically, strict liability is a concept that allows corporations to be charged with criminal responsibility as a consequence of the developments that occur. The impact of the abolition of the principle, namely, the system of proving faults will be increasingly difficult in enforcing environmental law, the more environmental damage that occurs, the government and society must spend more in proving errors that result in environmental damage, the court will be very rigid in giving decisions if they have to be bound by the new norm in the omnibus law